Assessment of risk factors for suicidal behavior: results from the Tehran University of Medical Sciences Employees' Cohort study - Rezaei, Zahed; Mohammadi, Samira; Aghaei, Abbas; Pouragha, Hamidreza; Latifi, Arman; Keshavarz-Mohammadi, Nastaran (Frontiers in Public Health, 2023)
Introduction Suicide is a major issue of concern for public health. It is estimated that suicide accounts for 700,000 deaths every year. A personal history of one or more suicide attempts is the most important determinant of suicide among the general population. This study aimed to assess the major risk factors associated with suicidal behaviors among Iranian employees in a medical setting. Methods In this study, 3,913 employees of Tehran University of Medical Sciences who participated in the employees' cohort study conducted by the university were recruited. Suicidal behaviors (SBs) and their associated risk factors were evaluated using the World Mental Health Composite International Diagnostic Interview (CIDI) Version 3.0. Univariate and multivariate logistic regressions were performed to identify the determinants of SBs among the participants, and crude and adjusted odds ratios (ORs) with corresponding 95% confidence intervals (95% CIs) were calculated. Results Overall, 49.6% of respondents (n = 1,939) reported that they were tired of life and thinking about death. The lifetime prevalence rate of suicidal ideation (SI) was 8.1% (n = 317), that of suicide planning (SP) was 7.3% (n = 287), and that of suicide attempts (SA) was 3.1% (n = 122). Being female (OR: 1.87, CI: 1.64–2.12), being divorced (OR: 3.13, CI: 1.88–5.22), having a low level of education (OR: 1.57, CI: 1.15–2.14), and working in clinical and medical services (OR: 1.25, CI: 1.09–1.43) were associated with being tired of life and thinking about death. These factors were also associated with SI, SP, and SA. Discussion These findings highlight the need to prioritize mental health for suicide prevention, especially for high-risk groups, in workplace mental health promotion programs and policies.